Perubahan Sosial Masyarakat Adat Pasca Pelarangan Pembakaran Lahan Di Desa Lopus Kabupaten Lamandau - Nina Putri Hayam Dey; Brian L Djumaty (Universitas Muhammadiyah Ponorogo, 2021)
Local wisdom of the Dayak Tomun Lamandau community regarding opening agricultural land by burning is local knowledge that has been passed down from ancestors. In the activity of opening agricultural land there are rituals and customary rules that must be carried out. The rise of forest and land fires in recent years has caused negative impacts. Based on that, the government issued a policy prohibiting clearing forests and land by burning. The ban was felt by indigenous peoples in the village of Lopus where rice production to meet their daily lives fell sharply. This study aims to determine and analyze the social changes of indigenous peoples after the ban on land burning in Lopus Village, Lamandau Regency. While the research approach used is descriptive qualitative. Based on the findings in the field of social changes that occurred in Lopus Village not only because of policies that have been issued by the government but there are also other factors such as land conversion and increasing population. The inclusion of tourism is considered a form of local community survival strategy because it has an economic impact. The conclusion obtained is that until now the people of Lopus still burn land for farming but groups and land area have been restricted, so that the fields cannot meet household needs. To survive amid the prohibition of burning land, the indigenous people of Lopus Village have developed their cultural and natural tourism. Every year foreign and local tourists visiting the village of Lopus have increased, thus affecting the economy of indigenous peoples